The Structural Origins of Unearned Status: How Arbitrary Changes in Categories Affect Status Position and Market Impact. (September 2018) - Bowers, Anne; Prato, Matteo
Focusing on the categorical nature of many status orderings, we examine the relationship among status, actors' quality, and market outcomes. As markets evolve, the number of categories that structure them can increase, creating opportunities for new actors to be bestowed status, or it can decrease, dethroning certain actors from their superior standing. In both cases, gains and losses of status may occur without changes in actors' quality. Because audiences rely on status signals to infer the value of market actors, these exogenously generated status shifts can translate into changes in how audiences perceive actors, resulting in benefits for unearned status gains and costs for unearned status losses. We find support for our hypotheses in a sample of equity analysts at U.S. brokerage firms. Using data on the coveted Institutional Investor magazine All-Star award, we find that analysts whose status increases because of a category addition see corresponding increases in the stock market's response to their earnings estimates, while those who lose status see corresponding reductions. Our results suggest that the greater weight accorded to high-status actors may be misguided if that status occurs for structural reasons such as category changes rather than because of an actor's own quality.